Lamins at the crossroads of mechanosignaling - Osmanagic-Myers, Selma; Dechat, Thomas; Foisner, Roland (Genes & development, 2015)
The intermediate filament proteins, A- and B-type lamins, form the nuclear lamina scaffold adjacent to the inner nuclear membrane. B-type lamins confer elasticity, while A-type lamins lend viscosity and stiffness to nuclei. Lamins also contribute to chromatin regulation and various signaling pathways affecting gene expression. The mechanical roles of lamins and their functions in gene regulation are often viewed as independent activities, but recent findings suggest a highly cross-linked and interdependent regulation of these different functions, particularly in mechanosignaling. In this newly emerging concept, lamins act as a "mechanostat" that senses forces from outside and responds to tension by reinforcing the cytoskeleton and the extracellular matrix. A-type lamins, emerin, and the linker of the nucleoskeleton and cytoskeleton (LINC) complex directly transmit forces from the extracellular matrix into the nucleus. These mechanical forces lead to changes in the molecular structure, modification, and assembly state of A-type lamins. This in turn activates a tension-induced "inside-out signaling" through which the nucleus feeds back to the cytoskeleton and the extracellular matrix to balance outside and inside forces. These functions regulate differentiation and may be impaired in lamin-linked diseases, leading to cellular phenotypes, particularly in mechanical load-bearing tissues.